Perubahan Sifat Mekanis Komposit Hibrid Polyester yang Diperkuat Serat Sabut Kelapa dan Serat Ampas Empulur Sagu - Leiwakabessy, Arthur Yanny; Purnowidodo, Anindito; Sugiarto, Sugiarto; Soenoko, Rudy (Jurnal Rekayasa Mesin, 2013)
Filler composite material with natural fibers is ranging widely known in the manufacturing industry. Environmentally friendly material, able to be recycled, as well as able to destroy it self by nature is a technological demands of today. Coco fiber and pith of sago pulp fiber are natural fibers that derived from the processing of waste coconut and sago palms are abundant in the Moluccas and they have not been used optimally. Both of these materials can be used for the manufacture of composite, using polyester resin as the matrix. The research emphasis to get the maximum value of variation of fiber volume fraction and fiber coir pith of sago waste to the value of bending strength and impact strength, according to the desired application. Research methods Lay Hands Up in the manufacture of hybrid fiber composites with a combination of coconut fiber (SSK): sago pith pulp fibers (SES) with a variation of 10% SSK: SES40%, 20% SSK: SES30%, 30% SSK: SES20%, 40% SSK: SES10%. Dependent variable in the study is the bending strength and impact strength. The result is that an increase in bending strength and impact strength with increasing volume fraction, which is higher than the hybrid fiber coir fiber and coconut fiber pith of sago waste. The highest bending strength of the fiber volume fraction of 30%SSK: SES20%, amounting to 97 354 MPa, and the lowest bending force on the fiber volume fraction of 10% SSK: SES40% of 73 701 MPa, while the highest value of impact strength at SSK fiber volume fraction of 40% :SES10%, at 0178 J/mmÂ², and the lowest value of the impact strength on the fiber volume fraction of 10% SSK : SES40% at 0.053 J/mmÂ².Keywords: Mechanical Properties, composites hybrid, polyester, coconut coir fiber, fiber pulp sago pith.